Giovanni la Ravenna e il suo carteggio con Pier Paolo Vergerio - Papo, Adriano (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Giovanni da Ravenna is one of the most distinctive and original humanists of the XIV century. He was born in 1343 in Buda, where his father, Conversino da Frignano, was employed as official doctor at the court of Louis I the Great. After the untimely death of his mother, Giovanni was taken to Ravenna, which became his adoptive town. His life was eventful, often given to pleasure: he was a restless traveller; he studied in Ravenna, Ferrara, Bologna, Padua; he taught in Bologna, Florence, Ferrara, Conegliano, Belluno, Udine, Venice, Padua, Muggia; he acted as notary in Florence and Ragusa, as chancellor in Padua at the court of Francis I of Carrara. He was also a model pedagogue. The aim of the present paper is to examine closely his correspondence with Pier Paolo Vergerio, who had been one of his students at Padua university. The main correspondence between the two humanists belongs to the period of Giovanni’s stay in the little Istrian town of Muggia (1406-1408), in the neighbourhood of Trieste, which he had already visited in September 1395 as ambassador of Francis I of Carrara.